Endoscopic management of urolithiasis in pediatric and adolescence population in Hospital Universiti Sains Malaysia from year 2001 TO 2009 - Ismail, Azlinda (2013)
Urolithiasis affects between five to ten percent of human population during their lifetime, only one to three percent of whom are children (Desai, 2005). There are many causes of this disease such as metabolic abnormalities, urinary infection and anatomical abnormalities. Management modality of pediatric urolithiasis has shifted from open surgery to minimally invasive techniques. Currently, the majority of stones in children can be managed either with shock-wave lithothripsy (SWL) or endoscopic procedures like percutaenous nephrolithotripsy (PCNL), ureterorenoscopy (URS), vesicolithotripsy or combination of these modalities. Hospital Universiti Sains Malaysia (HUSM) is the one of referral centre in the east coast area for pediatric stone management. HUSM started to manage urolithiasis in pediatric endoscopically since 2001 until present. We started to have Extracorporal Shock-wave lithotripsy (ESWL) in 2008. Here we retrospectively review our nine years experiences in managing pediatric urolithiasis with endoscopic procedures from 2001 till 2009. We evaluated the efficacy and safety of the endoscopic procedures focusing on stone clearance and complications such as hematuria, sepsis, urinary perforation and hydrothorax. In this study, we also compare the serum creatinine before and after the procedure. Patients’ notes, investigation results, operative procedure, and complications after the procedure were reviewed. In this series, total 17 patients were included. Their age ranges from 1.8 to 18 years old, median age was 10 years old. Male to female ratio was about 4.7:1, male 14, female 3 patients. Majority were Malays, sixteen patients with only one Chinese. Sixteen patients presented with symptoms, such as pain (59%), fever (53%), heamaturia (47%), stone in urine (23%) and acute urinary retention (6%). One patient had family history of urinary stone, eight patients had other underlying disease and five patients had anatomical abnormality. Total numbers of procedures were 24 URS, nine PCNL, six vesicolithotripsy, three vesicolithotomy, five ESWL and one open heminephrectomy. Out of these procedures only eight percent was open surgery and the majorities, ninety two percent, were minimally invasive procedures. Among the minimally invasive procedures, 82% (39) were managed endoscopically. Endoscopic management in our centre contributed to incidence of heamaturia of 30.7%, ranging from one to five days (median two days), 23% of fever with range one to three days (median one day) and five percent (two cases) had ureteric perforation. In our series, there were no cases of sepsis, hydrothorax, or conversion to open surgery reported. In conclusion, our endoscopic procedures were safe and effective comparable with other studies.